Determinants of survival of human immune deficiency virus infected children after commencing anti-retroviral therapy in Kembata-Tembaro zone: A facility-based retrospective cohort study - Tarekegn Tessema; Mitiku Desalegn; Lonsako Abute; Tadele Yohannes (Global Pediatrics)
Background: HIV infection is one of the most significant challenges to global health faced by care providers. On the other hand, malnutrition is prevalent in developing countries; it remains a serious problem among HIV-positive children even with the provision of Anti-Retroviral Therapy (ART). Objective: To explore determinants of survival of human immune deficiency virus-infected children after commencing Anti-Retroviral Therapy in Kembata-Tembaro Zone, Southern Ethiopia, 2022. Methods: A facility-based retrospective cohort study was employed among 305 HIV-infected children on ART from May 5-June 4/2022 at public hospitals in Kembata-tembaro zone. The data were collected by using a checklist. Data were entered and cleaned using Epi info 3.5.3 and analysed using SPSS version 25.0 software. The cumulative survival time after initiation of ART was calculated using the Kaplan-Meier survival curve. A Multivariable Cox proportional model was fitted to identify factors affecting survival after initiation of ART and variables having P value≤ 0.05 were considered statistically significant predictors of mortality. Results: Overall, 43(14.1 %) died with an overall survival rate of 3.3 per 1000 child-months of observation. Undernourished children had a lower survival time than well-nourished children with mean survival time of 92.7 and 62.3 months respectively. Children with advanced WHO clinical stage III or IV (AHR: 6.1; 95 %CI: 1.4, 26.7), severe wasting at the baseline (AHR: 8.7; 95 %CI: 3.2, 23.6), high viral load level (AHR: 3.5; 95 %CI: 0.15, 0.61) and fair/poor adherence to ART (AHR: 3.7; 95 %CI: 2.3, 13.5) were significantly associated with survival of HIV-positive children in this study. Conclusion: a significant difference in survival time was observed between undernourished and well-nourished children with a high rate of mortality. Severe wasting, WHO clinical stage III or IV, high viral load level and fair/poor adherence were identified as the determinants of survival.